Dietary intakes in relation to nutrition recommendations and dietary quality in an Iranian adult population: the results of the Food and Nutrition Surveillance (FNS) - Najmeh Seifi; Nasrin Talkhi; Zahra Khorasanchi; Sara Saffar Soflaei; Seyyed Reza Sobhani; Zahra Abdollahi; Ali Mottaghi Moghaddam Shahri; Maryam Mohammadi-BajgIran; Gordon A. Ferns; Habibollah Esmaily; Majid Ghayour-Mobarhan (Journal of Health, Population and Nutrition)
Abstract Background The Iranian population faces a dual burden of overconsumption and nutrient insufficiency. Considering recent socioeconomic changes due to severe sanctions and the impact of the COVID-19 crisis, this research aimed to assess the energy, macronutrient, and micronutrient intakes of Iranian adults (19–60 years) and elderly individuals (> 60 years), based on the Food and Drug Administration dietary intake recommendations, through a survey. Methods This was a cross-sectional survey conducted from 2021 to 2022. The study included 1697 adults aged over18 years, selected from 11 geographical zones of Iran based on socio-economic and geographic similarities. All participants underwent dietary assessment using a validated 65-item Food Frequency Questionnaire (FFQ). Macronutrient and micronutrient intakes were compared with Dietary Reference Intakes (DRI). The Dietary Quality Index- International (DQI-I) was also calculated. Results In the adults aged 19–60 years, the mean usual energy intake was 2,321.64 ± 33.16 kcal/day. Carbohydrates, fat, and protein constituted 50.4%, 38.3%, and 13.45% of total energy intake, respectively. About 64.0% of women and 78.0% of men consumed fiber in amounts lower than recommended. The percentage of insufficiency was approximately 100% for retinol and vitamin D in both genders. Insufficient folate intake was 90.1% in women and 89.9% in men (p = 0.038). Excess sodium intake was more prevalent in men (p = 0.003). In the elderly (> 60 years), the mean usual energy intake was 1,987 kcal/day. Carbohydrates, fat, and protein constituted 52.98%, 35.88%, and 13.9% of total energy intake, respectively. The percentage of insufficiency for vitamin D, retinol, folate, selenium, and potassium intake was high (more than 80%) in both genders. Zinc insufficiency and excess sodium intake were significantly more prevalent in men. Conclusions This study indicated that carbohydrate and protein intakes were within the recommended ranges, while fat consumption was elevated in both adults and the elderly. Widespread micronutrient insufficiencies- especially in retinol, folate, vitamin D, potassium, and selenium- were evident across both genders and age groups. Excessive sodium consumption was more prevalent in men, along with a higher prevalence of zinc deficiency. These findings highlight the need for targeted dietary interventions to address nutritional gaps and promote healthier eating habits.